Challenges Faced by the Implementation of E-learning Educational Approach during the Covid-19 Pandemic Disease - Habarurema, Gratien; Mukabagorora, Theonille; Mukiza, Janvier (Journal of Education Technology, 2022)
The rapid growth of distance education within higher education has been encouraged particularly during school closure. This study was conducted within a consortium public university aiming to investigate the challenges faced upon the inclusion of e-learning approach during the Covid-19. This study is using a quantitative descriptive approach. One hundred and five (105) students registered in the undergraduate programs and thirty-seven (37) teaching staff of the public teaching colleges participated in this report, and the final number of participants was 142. Data were collected on a random basis and the results were analyzed using SPSS. Although this effort was made, a number of limitations was experienced, and showed by 62 (59%) of students that reported a financial crisis, 26.7% students and 8.1% facilitators with a limitation to connectivity, 37.1% students could not benefit e-tutorial practice whereas 13 (35.1 %) moderators could not be able to facilitate students remotely, the participants that could not effectively access the recommended e-learning platforms, 35 (33.3 %) students and 6 (16.2 %) facilitators. The overall observation showed that the e-learning-teaching strategy promoted the continuous schooling from home, but students from disadvantaged families and/or rural areas in particular experienced various limitations.